Gut-resident Phascolarctobacterium succinatutens decreases fat accumulation via MYC-driven epigenetic regulation of arginine biosynthesis - Qun Lan; Sui Liufu; Bohe Chen; Kaiming Wang; Wenwu Chen; Lanlin Xiao; Xiaolin Liu; Lei Yi; Jingwen Liu; Xin Xu; Caihong Liu; Mei Liu; et al. (npj Biofilms and Microbiomes)
Abstract Uncovering the mechanisms of excessive fat accumulation in livestock can not only protect animal health but also maintain the revenue of the intensive feeding industry. In this study, a bacteria-wide association study was conducted in a cohort of 129 commercial Yorkshire pigs. We found that Phascolarctobacterium succinatutens (P. succinatutens) was a key bacterium with greater abundance in low backfat thickness (LBF) pigs and was positively correlated with serum arginine concentrations. Fecal microbiota transplantation (FMT) experiment verified the beneficial roles of P. succinatutens in intestinal and lipid homeostasis. Administration of P. succinatutens in mice curbed weight gain, reduced adipocyte size, attenuated gut inflammation aggravation, and elevated circulating arginine levels. Propionate, a main metabolite produced by P. succinatutens, played a significant role in the above effects. Mechanistically, we indicated that P. succinatutens-generated propionate alleviated colonic inflammation by inhibiting the TLR4 signaling cascade. Importantly, propionate was found to stimulate the de novo synthesis of arginine by inhibiting the chromatin accessibility of MYC near the intron region. Finally, we found that the increase of arginine induced by P. succinatutens reduced fat deposition by suppressing the PI3K/Akt/FOXO3a signaling pathway. Our work provides novel insights into the epigenetic regulation of probiotic-mediated anti-obesity effects and highlights the potential of P. succinatutens in combating excessive obesity in commercial pigs.